Extended rotation flap for reconstruction of partial thickness defects of the tip and nasal ala region: in search of better aesthetic results - Annachiara Cavaliere; Barbara Maisto; Tatiana Zaporojan; Ludovica Giordano; Luigi Sorbino; Antonio Zaffiro; Amalia Vozza; Simone La Padula; Francesco D'Andrea; Fabrizio Schonauer (JPRAS Open, 2021)
Background: Basal cell carcinoma is the most common non-melanoma skin cancer of the nose. Defects of the nasal ala and tip region are among the most difficult to repair due to their intrinsic characteristics. Objective: To present our experience with the extended rotation flap for reconstruction of nasal ala defects and evaluate the outcome using the Patient and Observer Scar Assessment Scale (POSAS). Methods and Materials: Twenty-two patients with partial thickness nasal ala defects reconstructed using the extended rotation flap were assessed. Final cosmetic and functional outcomes were evaluated using the POSAS. Results: Flaps survived in all the reported cases and no major complication was recorded. Histology showed complete excision of the tumour in all cases. Using the POSAS, the mean overall evaluation for patients was 1.8/10, while the mean overall evaluation for the evaluation panel was 2.2/ 10. Conclusion: Although similar flaps have been previously described, the extended rotation flap for nasal ala and tip reconstruction represents a functionally and cosmetically appealing wound closure option, respecting and avoiding any distortion of the alar crease.